2022
DOI: 10.1155/2022/9096436
|View full text |Cite
|
Sign up to set email alerts
|

METTL14 Regulates Intestine Cellular Senescence through m6A Modification of Lamin B Receptor

Abstract: N-6-Methyladenosine (m6A) modification is involved in multiple biological processes including aging. However, the regulation of m6A methyltransferase-like 14 (METTL14) in aging remains unclear. Here, we revealed that the level of m6A modification and the expression of METTL14 were particularly decreased in the intestine of aged mice as compared to young mice. Similar results were confirmed in Drosophila melanogaster. Knockdown of Mettl14 in Drosophila resulted in a short lifespan, associated disrupted intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The levels of m 6 A modification decrease in mouse intestine as a consequence of aging. 620 Further study demonstrated METTL14-mediated m 6 A methylation is required for intestinal integrity and normal lifespan of Drosophila melanogaster , partly through the downstream target, Lamin B receptor (LBR). 620 Reduced expression of FTO and ensuing elevated m 6 A level occur in the aged mouse ovary, as well as in granulosa cells of the aged human ovary.…”
Section: Methylation In Neurological Disorders Cancer and Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of m 6 A modification decrease in mouse intestine as a consequence of aging. 620 Further study demonstrated METTL14-mediated m 6 A methylation is required for intestinal integrity and normal lifespan of Drosophila melanogaster , partly through the downstream target, Lamin B receptor (LBR). 620 Reduced expression of FTO and ensuing elevated m 6 A level occur in the aged mouse ovary, as well as in granulosa cells of the aged human ovary.…”
Section: Methylation In Neurological Disorders Cancer and Agingmentioning
confidence: 99%
“… 620 Further study demonstrated METTL14-mediated m 6 A methylation is required for intestinal integrity and normal lifespan of Drosophila melanogaster , partly through the downstream target, Lamin B receptor (LBR). 620 Reduced expression of FTO and ensuing elevated m 6 A level occur in the aged mouse ovary, as well as in granulosa cells of the aged human ovary. 621 , 622 Consequently, the degradation of a key downstream target mRNA, FOS, is interrupted with the help of reader protein IGF2BP2, contributing to ovarian aging.…”
Section: Methylation In Neurological Disorders Cancer and Agingmentioning
confidence: 99%
“…Lamin B1, a nuclear layer factor down-regulated in senescent cells, is involved in the regulation of subtelomere genes [ 82 ]. The knockdown of METTL14 reduced the m 6 A level of the lamin B receptor, leading to instability of the lamin B receptor mRNA, which in turn leads to cellular senescence [ 83 ].…”
Section: Cellular Aging Biomarkersmentioning
confidence: 99%
“…Further cellular experiments revealed that reducing METTL14 led to a decrease in m6A modification in lamin B receptor (LBR) mRNA. This instability in LBR mRNA triggered intestinal cellular senescence [ 114 ]. In LPS-stimulated IECs, suppressing the expression of METTL3 resulted in inhibited cell apoptosis, accompanied by a significant reduction in cleaved-caspase3 and cleaved-caspase9 protein levels [ 115 ].…”
Section: Mechanical Barrier Of the Intestine And M6amentioning
confidence: 99%